Reconstruction of last glacial climate in the Northern Andes through the analysis of subfossil woods (2017)
The reconstruction of tropical Andean past climates is limited by the scarcity of appropriate paleoenvironmental records, creating a gap in the comprehension of tropical premontane ecosystems during past climatic extremes. Last Glacial Volcano-clastic fan deposits of Colombian Central Cordillera provide a unique possibility to study the tropical vegetation response to past climatic changes in an area of main biological and cultural importance. We analyzed the microanatomical features of a mummified wood dated to represent a time window of the Last Glacial, most likely between 120-50kyr. The wood was identified as Jacaranda copaia (Bignoniaceae). Based on the current distribution of J.copaia specimens from herbaria, we modeled the potential paleodistribution of the species under glacial conditions using ecological modeling techniques, meanwhile the results were challenged by empirical evidence. Our findings suggest that the presence of J.copaia at 2000 m altitude in the past imply necessarily a warmer climate than today, and microanatomical features suggest more seasonal conditions than present